Synthesis and application of Cu(II) immobilized MCM-41 based solid Lewis acid catalyst for aminolysis reaction under solvent-free condition. (1st October 2021) - Chaudhary, Garima; Gupta, Neha; Singh, Amit Pratap
Graphical abstract: Abstract: In this paper, a Cu(II) immobilized periodic mesoporous organosilica (PMOs) was synthesized and used as a reusable solid Lewis acid catalyst for the aminolysis of epoxides under solvent-free conditions. An amide-based ligand, l -propylsilyl (1 ) having a specific binding pocket was prepared and fabricated on mesoporous MCM-41 to produce mesoporous organosilica l -propylsilyl@MCM-41 (2 ). Further, it has been utilized for anchoring Cu(II) ions under controlled reaction conditions to yield solid Lewis acid catalyst Cu(II)-l -propylsilyl@MCM-41 (3 ). The synthesized catalyst 3 exhibits significantly higher catalytic activity for aminolysis compared to hitherto known solid Lewis acid catalysts. An extensive range of β-amino alcohols with high regio and stereoselectivity were prepared by using catalyst 3 . The catalyst was recovered easily and reused eight times without any loss in its catalytic activity. Furthermore, the synthesis of clinically significant propranolol (β-blocker) from α- naphthyl glycidyl ether was attained successfully using catalyst 3 in a very decent yield.